Modeling of a Glow Discharge in a Coaxial System of Electrodes - Ольга Володимирівна Андрієнко; Сергій Борисович Сидоренко; Сергій Олексійович Майкут; Леонід Юрійович Цибульский; Анатолій Іванович Кузьмичєв (Mìkrosistemi, Elektronìka ta Akustika)
Modeling of a glow discharge in a cylindrical coaxial system with dielectric ends of electrodes in the hydrodynamic drift-diffusion approximation was performed. Model parameters: outer cathode diameter 10 and 13 mm, anode diameter 2 mm, voltage 2800 V, gas temperature 300 K. pd ~ 1 Pa∙m, which corresponds to the left side of the minimum area of the Paschen curve for discharge ignition. Reactions of ionization of atoms by electron impact, generation and quenching of metastable atoms, elastic collision of electrons with atoms and elastic collision of ions, resonant recharging of ions, Penning ionization, as well as secondary ion-electron emission of the cathode were taken into account. The distribution of potential and concentration of charged particles in the interelectrode space, the density of ion and electron currents were calculated within the framework of a self-consistent problem, and the current-voltage characteristics for two modes of discharge - plasma and plasma-free - were presented. The effect of pd on the parameters and discharge mode is determined. The obtained results can be used in plasma technologies for modification of the internal surfaces of metal, hollow, long parts with a small cross-sectional size, that is, in conditions close to those complicated by the occurrence of a discharge.